EXPLORING THE MODEL OF SOCIAL SECURITY IN THE CONTEXT OF MARKETING MACROENVIRONMENT ANALISIS - KHRUPOVYCH, Svitlana; MAZUR, Oleksandr; SLYVIAK, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the impact of social security systems on consumer purchasing power, highlighting the economic dimension of the marketing macroenvironment as a key factor shaping consumer behavior—especially under conditions of political instability and wartime disruption in Ukraine. Particular attention is given to the most vulnerable market segment: citizens receiving minimum pensions or wages. The authors emphasize that under martial law in Ukraine, these factors become particularly significant due to a substantial decline in real demand across most product categories. It is estimated that approximately 16.5% of Ukraine's adult population lives on these minimum social payments. The study provides a theoretical overview of classic welfare models, including liberal, conservative, social-democratic, Mediterranean, and post-socialist types. It outlines the main characteristics of each model and presents examples of countries where these models have shaped national social policy. The analysis emphasizes that in countries with a large proportion of low-income citizens, such as Ukraine, social guarantees are a critical foundation for pricing strategies in business. A comparative case study between Ukraine and Hungary—both classified under the post-socialist welfare model—is presented, revealing differing approaches to implementing social protection principles. The findings confirm that social payments in Ukraine are critically low and insufficient to cover basic needs such as food, utilities, and healthcare. The article argues for a rethinking of domestic marketing strategies during wartime. It suggests a shift in both pricing and product strategies toward the economically disadvantaged segment, which represents one-sixth of the adult population. Drawing from international practices in welfare reform, the study proposes marketing programs tailored to current social realities. Practical recommendations are offered for businesses to plan and deliver accessible goods and services for low-income groups. Practical recommendations have been formulated for businesses regarding the marketing planning of affordable goods and services targeted at low-income consumers.
Keywords: social security model; marketing environment; minimum pension; minimum wage; market segment; marketing strategy